Simple whole cell based high throughput screening protocol using Mycobacterium bovis BCG for inhibitors against dormant and active tubercle bacilli - Khan, Arshad; Sarkar, Dhiman (Journal of Microbiological Methods, 2008)
This study aimed at developing a whole cell based high throughput screening protocol to identify inhibitors against both active and dormant tubercle bacilli. A respiratory type of nitrate reductase (NarGHJI), which was induced during dormancy, could reflect the viability of dormant bacilli of Mycobacterium bovis BCG in microplate adopted model of in vitro dormancy. Correlation between reduction in viability and nitrate reductase activity was seen clearly when dormant stage inhibitor metronidazole and itaconic anhydride were applied in this in vitro microplate model. Active replicating stage could also be monitored in the same assay by measuring the A(620) of the culture. MIC values of 0.08, 0.075, 0.3 and 3.0 mu g/ml, determined through monitoring A(620) in this assay for rifampin, isoniazid, streptomycin and ethambutol respectively, were well in agreement with previously reported by BACTEC and Bio-Siv assays. S/N ratio and Z' factor for the assay were 8.5 and 0.81 respectively which indicated the robustness of the protocol. Altogether the assay provides an easy, inexpensive, rapid, robust and high content screening too] to search novel antitubercular molecules against both active and dormant bacilli. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: high throughput screening; tuberculosis; Wayne's dormancy model; whole cell based assay

Self–assembled histidine acid phosphate nanocapsules as templates for multifunctional hollow platinum nanospheres in ionic liquid [BMIM][BF 4 ] for drug delivery - Soni, Sarvesh Kumar; Sarkar, Sampa; Sarkar, Dhiman; Coloe, Peter J.; Bhargava, Suresh Kumar; Bansal, Vipul (Proceedings of Chemeca, 2012)
During the past few decades, the design and fabrication of nano drug delivery vehicle has received considerable attention for incorporating multi-functionality, emphasizing transportation of anticancer drugs to tumour sites. Protein-based nanoparticles hold significant promise in the development of anticancer drug delivery systems since they have remarkable superiority in biocompatibility, biodegradability and natural metabolism in physiologic systems. Ionic liquids (ILs) are a class of solvents that are composed solely of ions (ILs – commonly referred as room temperature molten salts or room temperature ionic liquids). They have recently emerged as green solvents or green reaction media, because of their reported unique physico-chemical properties. We report for the first time the controlled self-assembly of Histidine Acid phosphatase (HAP) enzyme in the IL 1-butyl-3-methylimidazolium tetrafluoroborate [BMIM][BF 4 ], leading to the formation of HAP nanocapsules as template for synthesis of platinum nanospheres. These HAP nano-containers were loaded with an anticancer drug curcumin. We further demonstrated in vitro drug release and synergistic anticancer effect of these systems on three different cell lines viz. hepatocellular carcinoma (HepG2), breast cancer (MCF-7) and human acute monocytes (THP-1). The present work can extend our theoretical understanding on nano-bio interfacial molecular self assembly and will facilitate the motivated insights of inorganic/organic hybrid nano-materials/ nano-particles/ nano-objects and ionic liquids based multi functional drug delivery vehicles with synergistic combination chemotherapy for potential application in tumor targeting. INTRODUCTION During the past few decades, the design and fabrication of drug delivery vehicle has received considerable attention for incorporating multi-functionality emphasizing transportation of anticancer drugs to tumour sites. These nano drug delivery vehicles have many advantages including prolonged circulation time of the drugs (Duncan, 2003, Kiick, 2007) , improved drug targeting and solubility (Duncan, 2003, Kiick, 2007), higher payloads (Duncan, 2003) and controlled release of the therapeutics into the blood stream or the targeted tumour tissues (Uhrich et al. 1999, Duncan, 2003).

Sophorolipid assisted tunable and rapid gelation of silk fibroin to form porous biomedical scaffolds - Dubey, Parul; Nawale, Laxman; Sarkar, Dhiman; Nisal, Anuya; Prabhune, Asmita (RSC Advances, 2015)
Three dimensional polymer hydrogels, based on both natural and synthetic polymers, are increasingly being used as scaffolds and drug delivery vehicles for biomedical applications. Fibrous protein, silk fibroin (SF), obtained from the Bombyx mori silkworm is a promising candidate in this area. However, SF has a long gelation time of about a few weeks that can only be reduced by non-physiological treatments (e. g. high temperature, ultrasonication and low pH) or by addition of a chemical and non-biodegradable polymer and/or surfactant. We report here accelerated gelation of SF under physiological conditions using a biosurfactant, sophorolipid (SL) as a gelling agent. SL and SF are completely miscible and form a very clear solution upon mixing. Hence it is interesting to see that this clear solution gels in a time span of just a few hours. The hydrogels so formed have pore architecture, porosities and mechanical stability ideally suited for tissue culture applications. Here we also demonstrate that mouse fibroblast cells not only adhere to but also extensively proliferate on these SF-SL scaffolds.

Synthesis and evaluation of thieno[2,3-d]pyrimidin-4(3H)-ones as potential antitubercular agents - Borate, Hanumant B.; Annadate, Ritesh A.; Vagh, Sandip S.; Pisal, Mahesh M.; Deokate, Sagar B.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Nawale, Laxman U.; Sarkar, Dhiman (MedChemComm, 2015)
A number of thieno[2,3-d]pyrimidin-4(3H)-ones were designed, synthesized and screened against Mycobacteria as a part of our program to develop new antitubercular agents. It was observed that some of the compounds have significant antimycobacterial activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743). The active compounds were studied for cytotoxicity against four cell lines and were found to be non-cytotoxic. The results showed that compounds 13b and 29e were found to exhibit very good antimycobacterial activity (MIC in the range of 6-8 mu M) and the thienopyrimidinones as a class have potential to be developed as antitubercular agents.

Shape and size engineered cellulosic nanomaterials as broad spectrum anti-microbial compounds - Sharma, Priyanka R.; Kamble, Sunil; Sarkar, Dhiman; Anand, Amitesh; Varma, Anjanikumar (International Journal of Biological Macromolecules, 2016)
Oxidized celluloses have been used for decades as antimicrobial wound gauzes and surgical cotton. We now report the successful synthesis of a next generation narrow size range (25-35 nm) spherical shaped nanoparticles of 2,3,6-tricarboxycellulose based on cellulose I structural features, for applications as new antimicrobial materials. This study adds to our previous study of 6-carboxycellulose. A wide range of bacteria such as Escherichia coli, Staphloccocus aureus, Bacillus subtilis and Mycobacterium tuberculosis (non-pathogenic as well as pathogenic strains) were affected by these polymers in in vitro studies. Activity against Mycobacteria were noted at high concentrations (MIC99 values 250-1000 mu g/ml, as compared to anti-TB drug Isoniazid 0.3 mu g/ml). However, the broad spectrum activity of oxidized celluloses and their nanoparticles against a wide range of bacteria, including Mycobacteria, show that these materials are promising new biocompatible and biodegradable drug delivery vehicles wherein they can play the dual role of being a drug encapsulant as well as a broad spectrum anti-microbial and anti-TB drug. (C) 2016 Published by Elsevier B.V.
Keywords: Anti-microbial; cellulose; Spherical nanoparticles; Tricarboxycellulose

Synthesis and antitubercular activity of new 1,3,4-oxadiazoles bearing pyridyl and thiazolyl scaffolds - Dhumal, Sambhaji T.; Deshmukh, Amarsinh R.; Bhosle, Manisha R.; Khedkar, Vijay M.; Nawale, Laxman U.; Sarkar, Dhiman; Mane, Ramrao A. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of more potent and safe new antitubercular agents, here new 2-pyridinyl substituted thiazolyl-5-aryl-1,3,4-oxadiazoles (6a-o), have been designed and synthesized using thionicotinamide as a starting, following novel multistep synthetic route. An intermediate, pyridinyl substituted thiazolyl acid hydrazide (4) when condensed with benzoic acids/nicotinic acids (5a-o) in the presence of silica supported POCl3 yielded better to excellent yields of the title compounds. All the synthesized compounds (6a-o) and intermediate acid hydrazide (4) have been screened for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB) and Mycobacterium bovis BCG. Amongst them, 6f, 6j, 6l and 6o have revealed promising activity against M. bovis BCG at concentrations less than 3 mu g/mL. These compounds have shown low cytotoxicity (CC50: > 100 mu g/mL) towards four human cancer cell lines. Molecular docking study has also been performed against mycobacterial enoyl reductase (InhA) enzyme to gain an insight into the binding modes of these molecules and recorded good binding affinity. The ADME properties the title products have also been analyzed. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: 1; 3; 4-Oxadiazole; Antitubercular activity; Cytotoxicity; Molecular docking; Pyridine; Thiazole

Synthesis and antitubercular activity of new benzo[b]thiophenes - Mahajan, Pravin S.; Nikam, Mukesh D.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman; Gill, Charansingh H. (ACS Medicinal Chemistry Letters, 2016)
In vitro and ex vivo efficacies of four series of benzo[b]thiophene-2-carboxylic acid derivatives were studied against Mycobacterium tuberculosis H37Ra (MTB). Benzo[b]thiophenes were also tested in vitro against multidrug resistant Mycobacterium tuberculosis H37Ra (MDR-MTB), and 7b was found to be highly active against A- and DMDR-MTB/MTB (MIC ranges 2.73-22.86 mu g/mL). The activity of all benzo[b]-thiophenes against M. bovis BCG (BCG) was also assessed grown under aerobic and under conditions of oxygen depletion. Compounds 8c and 8g showed significant activity with MICs of 0.60 and 0.61 mu g/mL against dormant BCG. The low cytotoxicity and high selectivity index data against human cancer cell lines, HeLa, Panc-1, and THP-1 indicate the potential importance of the development of benzo[b]thiophene-based 1,3-diketones and flavones as lead candidates to treat mycobacterial infections. Molecular docking studies into the active site of DprE1 (Decaprenylphosphoryl-beta-n-ribose-2'-epimerase) enzyme revealed a similar binding mode to native ligand in the crystal structure thereby helping to understand the ligand protein interactions and establish a structural basis for inhibition of MTB. In summary, its good activity in in vitro and ex vivo model, as well as its activity against multidrug-resistant M. tuberculosis H37Ra in a potentially latent state, makes 7b an attractive drug candidate for the therapy of tuberculosis.
Keywords: Benzo[b]thiophene; Cytotoxicity; M. Bovis BCG; MDR-MTB; Molecular docking

Synthesis and bioactivity of novel triazole incorporated benzothiazinone derivatives as antitubercular and antioxidant agent - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Arkile, Manisha A.; Khedkar, Vijay M.; Jadhav, Nandadeep J.; Sarkar, Dhiman; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of new active molecules against Mycobacterium tuberculosis (MTB) H37Ra and M. bovis BCG, a small focused library of benzothiazinone based 1,2,3-triazoles has been efficiently prepared via click chemistry approach. Several derivatives were found to be promising inhibitors of MTB and M. bovis BCG characterized by lower MIC values (27.34-29.37 mu g/mL). Among all the synthesized compounds, 6c and 6e is the most active compound against MTB and M. bovis BCG. The compounds were further tested for anti-proliferative activity against HeLa, A549 and A431 cell lines using MTT assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Further, the synthesized compounds were found to have potential antioxidant activity with IC50 range = 14.14-47.11 mu g/mL. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against a potential target MTB DprE1, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of the in vitro and in silico study suggest that the triazole incorporated benzothiazinone may possess the ideal structural requirements for further development of novel therapeutic agents. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-Triazole; ADME prediction; Antioxidant; Antitubercular; Docking study

Synthesis and docking studies of pyrazine-thiazolidinone hybrid scaffold targeting dormant tuberculosis - Chitre, T. S.; Asgaonkar, K. D.; Miniyar, P. B.; Dharme, A. B.; Arkile, Manisha A.; Yeware, A.; Sarkar, Dhiman; Khedkar, Vijay M.; Jha, Prakash C. (Bioorganic & Medicinal Chemistry Letters, 2016)
The persistence of Mycobacterium tuberculosis (MTB) in dormant stage assists the pathogen to develop resistance against current antimycobactrial drugs. To address this issue, we report herein the synthesis of N-(4-oxo-2 substituted thiazolidin-3yl) pyrazine-2-carbohydrazide derivatives designed by following the molecular hybridization approach using pyrazine and thiazolidenone scaffolds. The compounds were evaluated against MTB H37Ra and Mycobacterium bovis BCG in dormancy model. Most of the compounds had IC50 values in 0.3-1 mu g/ml range. The active compounds were further tested for anti-proliferative activity against THP-1, Panc-1, A549, and MCF-7 cell lines using MTT assay and exhibited no significant cytotoxicity. We also report molecular docking studies using active analogs and MTB Decaprenylphosphoryl-beta-D-ribose-2'-epimerase (DprE1) to rationalize the biological activity and to provide an insight into the probable mechanism of action and binding mode of hybridized structures. The results obtained validate the use of molecular hybridization approach and also suggest that reported compounds can provide a novel pharmacophore to synthesize lead compounds against dormat MTB. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: docking; Dormant; Hybrid design; Pyrazine; Thiazolidenone; tuberculosis

Synthesis and evaluation of thieno[2,3-d]pyrimidin-4(3H)-ones as potential antitubercular agents (vol 6, pg 2209, 2015) - Borate, Hanumant B.; Annadate, Ritesh A.; Vagh, Sandip S.; Pisal, Mahesh M.; Deokate, Sagar B.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Nawale, Laxman U.; Sarkar, Dhiman (Medchemcomm, 2016)

Synthesis and tyrosinase inhibition activity of trans-stilbene derivatives - Ismail, Tabasum; Shafi, Syed; Srinivas, Jada; Sarkar, Dhiman; Qurishi, Yasrib; Khazir, Jabeena; Alam, Mohammad Sarwar; Kumar, Halmuthur Mahabalarao Sampath (Bioorganic Chemistry, 2016)
Synthesis of a focussed library of trans-stilbene compounds through Wittig and other base catalysed condensation reactions is presented. The synthesized stilbenes were screened for their inhibitory potential against murine tyrosinase activity to explore the structure activity relationship (SAR). Presence of electron withdrawing group (-CN) at the double bond and hydroxyl group or halogen atom especially at para-position on the aromatic rings was found to significantly elevate the inhibitory activity. Among all the compounds screened, compounds 2, 6, 8, 10, 11, 15 and 21 were found to exhibit appreciable inhibitory activity. Compound 21 ((E)-2,3-bis(4-Hydroxyphenyl) acryonitrile) was found to be the most active with an IC50 value of 5.06 mu M which is less than half of the value 10.78 mu M observed for resveratrol (common standard used in murine tyrosinase activity studies) under similar conditions. The results obtained from the present study reveal structural/functional group sensitivity for the tyrosinase inhibitory activity of stilbenoid moieties and are expected to be very helpful for the design and synthesis of novel, selective and effective tyrosinase inhibitors. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Electron withdrawing groups; Murine tyrosinase activity; Resveratrol; Stilbenoids; Tyrosinase inhibitors; Wittig reaction

Synthesis, biological evaluation and molecular docking of novel coumarin incorporated triazoles as antitubercular, antioxidant and antimicrobial agents - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Shingate, Bapurao B.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Khedkar, Vijay M.; Nawale, Laxman; Sarkar, Dhiman; Navale, Govinda R.; Shinde, Sandip S. (Medicinal Chemistry Research, 2016)
A series of new coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular activity in vitro against Mycobacterium tuberculosis H37Ra, antioxidant activity by DPPH radical scavenging assay, antimicrobial activity in vitro against three gram-positive bacteria (Staphylococcus aureus, Micrococcus luteus and Bacillus cereus) and three gram-negative bacteria (Escherichia coli, Pseudomonas fluorescens and Flavobacterium devorans as well as three fungi (Aspergillus niger, Penicillium chrysogenum and Curvularia lunata). The bioactive assay showed that some synthesized coumarin triazoles displayed comparable or even better antitubercular, antioxidant, antibacterial and antifungal efficacy in comparison with reference drugs. Furthermore, docking study has been performed against DprE1 enzyme of M. tuberculosis that showed good binding interactions. Moreover, the synthesized compounds were also analyzed for ADME properties and showed potential to build up as good oral drug candidates. New coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular, antioxidant, antibacterial and antifungal activity. Some of the coumarin-based triazole derivatives displayed comparable or even better efficacy in comparison with reference drugs. Molecular docking study has been performed against DprE1 enzyme of Mycobacterium tuberculosis showed good binding interactions. [GRAPHICS] .
Keywords: 1; 2; 3-Triazole; ADME prediction; Antimicrobial; Antioxidant; Antitubercular; Click chemistry; Docking study

Synthesis, biological evaluation and molecular docking studies of N-acylheteroaryl hydrazone derivatives as antioxidant and anti-inflammatory agents - Mahajan, Pravin S.; Nikam, Mukesh D.; Khedkar, Vijay M.; Jha, Prakash C.; Sarkar, Dhiman; Gill, Charansingh H. (Research on Chemical Intermediates, 2016)
In search of new therapeutics with greater potency, three new series of 3-methyl-1-phenyl-1H-thieno[2,3-c]pyrazole-5-carbohydrazide derivatives have been synthesized and evaluated for their in vitro antioxidant and anti-inflammatory activities. The hydrazones bearing a core pyrazole, chromone and tetrazolo[1,5-a]quinoline scaffold showed promising activities. Interestingly, compounds 3a (EC50 = 06.00 +/- A 2.36) and 5c (EC50 = 07.21 +/- A 0.67) showed the most potent antioxidant activity, while compounds 3a (EC50 = 10.25 +/- A 1.08), 7b (EC50 = 10.50 +/- A 0.99) and 7c (EC50 = 11.18 +/- A 0.15) showed significant anti-inflammatory activity. Furthermore, molecular docking studies also revealed a significant correlation between the binding score and biological activity for these compounds to describe the molecular basis for the structure activity relationship (SAR) results. As these compounds are good cyclooxygenase inhibitors, isoenzyme inhibitory potency studies are warranted.
Keywords: Anti-inflammatory; Antioxidant; Docking study; N-Acylhydrazones; Structure-activity relationship

Synthesis, biological evaluation and molecular docking study of some novel indole and pyridine based 1,3,4-oxadiazole derivatives as potential antitubercular agents - Desai, N. C.; Somani, Hardik; Trivedi, Amit; Bhatt, Kandarp; Nawale, Laxman; Khedkar, Vijay M.; Jha, Prakash C.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2016)
A series of indole and pyridine based 1,3,4-oxadiazole derivatives 5a-t were synthesized and evaluated for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB) and Mycobacterium bovis BCG both in active and dormant state. Compounds 5b, 5e, 5g and 5q exhibited very good antitubercular activity. All the newly synthesized compounds 5a-t were further evaluated for antiproliferative activity against HeLa, A549 and PANC-1 cell lines using modified MTT assay and found to be noncytotoxic. On the basis of cytotoxicity and MIC values against Mycobacterium bovis BCG, selectivity index (SI) of most active compounds 5b, 5e, 5g and 5q was calculated (SI = GI(50)/MIC) in active and dormant state. Compounds 5b, 5e and 5g demonstrated SI values >= 10 against all three cell lines and were found to safe for advance screening. Compounds 5a-t were further screened for their antibacterial activity against four bacteria strains to assess their selectivity towards MTB. In addition, the molecular docking studies revealed the binding modes of these compounds in active site of enoyl reductase (InhA), which in turn helped to establish a structural basis of inhibition of mycobacteria. The potency, low cytotoxicity and selectivity of these compounds make them valid lead compounds for further optimization. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: 1; 3; 4-Oxadiazole; Antitubercular activity; Cytotoxicity; Indole; Molecular docking; Pyridine

Superoxide generation and its involvement in the growth of mycobacterium smegmatis - Yeware, Amar M.; Shurpali, Ketaki D.; Athalye, Meghana C.; Sarkar, Dhiman (Frontiers in Microbiology, 2017)
Superoxide generation is inevitable in aerobic organisms, most of which have developed mechanisms to detoxify superoxides. However, its significance has not been clearly understood in mycobacteria. This study demonstrates that NADH oxidase is the major source of superoxide in Mycobacterium smegmatis and elucidates the involvement of superoxide in M. smegmatis growth. The maximum inhibition of superoxide generation was observed in the presence of diphenyleneiodonium chloride (DPI), an NADH oxidase inhibitor, compared to other standard inhibitors. After incubation for 24 h, the number of colony forming units (CFUs) was reduced by 6.8 log10 compared to the untreated culture. The inhibitory effect of DPI on M. smegmatis was reversed when the same culture was supplemented with menadione and pyrogallol, which are superoxide generators. Thus, this study reports the source of superoxide generation and its involvement in the growth of M. smegmatis.

Synthesis and antimycobacterial screening of new thiazolyl-oxazole derivatives - Abhale, Yogita K.; Sasane, Amit V.; Chavan, Abhijit P.; Shekh, Saddam Husen; Deshmukh, Keshav K.; Bhansali, Sujit; Nawale, Laxman; Sarkar, Dhiman; Mhaske, Pravin C. (European Journal of Medicinal Chemistry, 2017)
In the present study a series of 4-methyl-2-aryl-5-(2-aryl/benzyl thiazol-4-yl) oxazole (4a-v) have been synthesized and evaluated for their preliminary antitubercular, antimicrobial and cytotoxicity activity. Among all the synthesized compounds, 4v reported comparable activity against dormant M. tuberculosis H37Ra and M. bovis BCG strains with respect to standard drug rifampicin. The active compounds from the antitubercular study were further tested for anti-proliferative activity against HeLa, A549 and PANC-1 cell lines using MU assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Further, the synthesized compounds were found to have potential antibacterial activities with MIC range of 2.1-26.8 mu g/mL. High potency, lower cytotoxicity and promising antimycobacterial activity suggested that these compounds could serve as good leads for further optimisation and development. (C) 2017 Elsevier Masson SAS. All rights reserved.

Synthesis and antitubercular activity of new thiazolidinones with pyrazinyl and thiazolyl scaffolds - Dhumal, Sambhaji T.; Deshmukh, Amarsinh R.; Khillare, Lalit D.; Arkile, Manisha A.; Sarkar, Dhiman; Mane, Ramrao A. (Journal of Heterocyclic Chemistry, 2017)
Emergence of multidrug resistant and extensively drug resistant tuberculosis has prompted to develop new molecular entities to treat the disease. A series of new 4-thiazolidinones with pyrazinyl and thiazolyl scaffolds has been synthesized, and their antitubercular activity is reported. The title 4-thiazolidinones, N-(pyrazinyl substituted thiazoloylamino)-2-aryl-4-thiazolidinones () have been first time prepared using pyrazinamide as a starting material via five successive steps. The purity and the structures of the intermediates (carboethoxythiazole, acid hydrazide, and azomethines) and title thiazolidinones () have been confirmed by TLC and spectral analyses, respectively. An antitubercular screening of the new 4-thiazolidinones has been performed on bacterial strains, Mycobacterium tuberculosis H37Ra and Mycobacterium BCG using the solutions of different concentrations of the compounds () and the screening results are presented. Compound has displayed notable antitubercular activity.

Synthesis and biological evaluation of 1,2,4-triazole-3-thione and 1,3,4-oxadiazole-2-thione as anti-mycobacterial agents - Sonawane, Amol; Rode, Navnath D.; Nawale, Laxman U.; Joshi, Rohini R.; Joshi, Ramesh A.; Likhite, Anjali P.; Sarkar, Dhiman (Chemical Biology & Drug Design, 2017)
Resistance among dormant mycobacteria leading to multi-drug resistant (MDR) and extremely-drug resistant(XDR) tuberculosis is one of the major threats. Hence, a series of 1,2,4-triazole-3-thione and 1,3,4-oxadiazole-2-thione derivatives (4a-5c) have been synthesised and screened for their anti-tubercular activity against Mycobacterium tuberculosis H37Ra (H37Ra). Thetriazolethiones4b and 4v showed high anti-tubercular activity (both MIC and IC50) against the dormant H37Ra by in vitro and ex vivo. They were shown to have more specificity towards mycobacteria than other gram-negative and gram- positive pathogenic bacteria. The cytotoxicity was almost insignificant up to 100 μg/mL against THP-1, A549 and PANC-1 human cancer cell lines, and solubility was high in aqueous solution, indicating the potential of developing these compounds further as novel therapeutics against tuberculosis infection.

Synthesis and biological evaluation of new fluconazole β-lactam conjugates linked via 1,2,3-triazole - Divse, Jaisingh M.; Mhaske, Santosh B.; Charolkar, Chaitanya R.; Sant, Duhita G.; Tupe, Santosh G.; Deshpande, Mukund V.; Khedkar, Vijay M.; Nawale, Laxman U.; Sarkar, Dhiman; Pore, Vandana S. (New Journal of Chemistry, 2017)
Novel 1,2,3-triazole-linked β-lactam–fluconazole conjugates 12(a–l) were designed and synthesized. The compounds showed potent antifungal activity against two pathogenic Candida strains; Candida albicans ATCC 24433 and Candida albicans ATCC 10231 with MIC values in the range of 0.0625–2 μg mL−1. Compounds 12h, 12j and 12k showed promising antifungal activity against all the tested fungal pathogens except C. neoformans ATCC 34554 compared to fluconazole. Compound 12j in which the β-lactam ring was formed using para-anisidine and benzaldehyde was found to be more potent than fluconazole against all the fungal strains with an IC50 value of <0.015 μg mL−1 for Candida albicans (ATCC 24433). Mechanistic studies for active compounds revealed that the antifungal action was due to ergosterol inhibition. Compounds 12h and 12j at a concentration of 0.125 μg mL−1 caused 91.5 and 96.8% ergosterol depletion, respectively, compared to fluconazole which at the same concentration caused 49% ergosterol depletion. The molecular docking study revealed that all the fluconazole β-lactam conjugates 12(a–l) could snugly fit into the active site of lanosterol 14α-demethylase (CYP51) with varying degrees of affinities. As anticipated, the binding energy for compound 12j (−58.961 kcal mol−1) was much smaller than that for fluconazole (−52.92 kcal mol−1). The synthesized compounds have therapeutic potential for the control of candidemia.

Synthesis and cell imaging applications of fluorescent mono/di/tri-heterocycl- yl-2,6-dicyanoanilines - Pisal, Mahesh M.; Annadate, Ritesh A.; Athalye, Meghana C.; Kumar, Dipak; Chavan, Subhash P.; Sarkar, Dhiman; Borate, Hanumant B. (Bioorganic & Medicinal Chemistry Letters, 2017)
Synthesis of 3,4,5-triheterocyclyl-2,6-dicyanoanilines, starting from heterocyclic aldehydes and 1,2-diheterocycle-substituted ethanones, is described. 2,6-Dicyanoanilines with one or two heterocyclic substituents have also been synthesized. It was found that some of these molecules have selective cell-staining properties useful for cell imaging applications. The compounds 1g, 10f and 11 were found to stain cytoplasm of the cells in contact but not the nucleus while the compound 12 showed affinity to apoptotic cells resulting in blue fluorescence. The cell imaging results with compound 12 were similar to Annexin V-FITC, a known reagent containing recombinant Annexin V conjugated to green-fluorescent FITC dye, used for detection of apoptotic cells. These compounds were found to be non-cytotoxic and have potential application as cell imaging agents.

Synthesis, antimycobacterial screening and molecular docking studies of 4-aryl-4′-methyl-2′-aryl-2,5′-bisthiazole derivatives - Abhale, Yogita K.; Shinde, Abhijit D.; Deshmukh, Keshav K.; Nawale, Laxman U.; Sarkar, Dhiman; Choudhari, Prafulla B.; Kumbhar, Santosh S.; Mhaske, Pravin C. (Medicinal Chemistry Research, 2017)
A series of 4-aryl-4′-methyl-2′-aryl-2,5′-bisthia- zole derivatives (5a–o) were synthesized and screened for inhibitory activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743) strains. Five lead compounds (5e, 5f, 5g, 5h, and 5o) were further confirmed from their dose dependent effect against MTB and Bovine–Calmette–Guerin. The most promising compounds 5f (MIC90: 11.32 μg/mL), 5h (MIC90: 11.59 μg/mL), and 5o (MIC90: 23.64 μg/mL) showed strong antitubercular activity against dormant MTB and BCG as well as almost insignificant cytotoxicity up to 100μg/mL against HeLa, A549, and PANC-1 human cancer cell lines. Further, the synthesized compounds were found to have potential antibacterial activity against Gram-negative bac- teria, Escherichia coli, Pseudomonas flurescence and Gram- positive bacteria, Staphylococcus aureus, Bacillus subtilis. Most of the synthesized compounds showed moderateactivity against fungal strain Candida albicans. Molecular docking studies of these compounds showed significant interactions with crystal structure of the cytochrome P45014α-sterol demethylase (CYP51) PDB ID: 1E9X. Hydrogen bond interactions with SER261 and VAL395 are important interactions for selective inhibition of designed inhibitors. Compounds 5f, 5h, and 5o showed significant interactions with 1E9X. All the experimental results promote us to consider this series as a starting point for the devel- opment of novel, selective and more potent antitubercular agents in the future.

Synthesis, biological evaluation, and molecular docking studies of novel 3-aryl-5-(alkyl-thio)-1H-1,2,4-triazoles derivatives targeting Mycobacterium tuberculosis - Rode, Navnath D.; Sonawane, Amol D.; Nawale, Laxman; Khedkar, Vijay M.; Joshi, Ramesh A.; Likhite, Anjali P.; Sarkar, Dhiman; Joshi, Rohini R. (Chemical Biology & Drug Design, 2017)
A small library of new 3-aryl-5-(alkyl-thio)-1H-1,2,4-triazoles was synthesized and screened for the antimycobacterial potency against Mycobacterium tuberculosis H37Ra strain and Mycobacterium bovis BCG both in active and dormant stage. Among the synthesized library, 25 compounds exhibited promising anti-TB activity in the range of IC(50)0.03-5.88g/ml for dormant stage and 20 compounds in the range of 0.03-6.96g/ml for active stage. Their lower toxicity (>100g/ml) and higher selectivity (SI=>10) against all cancer cell lines screened make them interesting compounds with potential antimycobacterial effects. Furthermore, to rationalize the observed biological activity data and to establish a structural basis for inhibition of M.tuberculosis, the molecular docking study was carried out against a potential target MTB CYP121 which revealed a significant correlation between the binding score and biological activity for these compounds. Cytotoxicity and in vivo pharmacokinetic studies suggested that 1,2,4-triazole analogues have an acceptable safety index, in vivo stability and bio-availability.

Synthesis of novel triazole-incorporated isatin derivatives as antifungal, antitubercular, and antioxidant agents and molecular docking study - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Nawale, Laxman; Arkile, Manisha A.; Sarkar, Dhiman; Shingate, Bapurao B. (Journal of Heterocyclic Chemistry, 2017)
A library of 1,2,3-triazoles efficiently prepared via click chemistry and evaluated for their antifungal, antitubercular, antioxidant, cytotoxicity, molecular docking and ADME prediction.

Synthesis and biological evaluation of new 2-aryl-4-((4-aryl-1H-1,2,3-triazol-1-yl)methyl)thiazole derivatives - Shinde, Vikas; Mahulikar, Pramod; Mhaske, Pravin C.; Nawale, Laxman; Sarkar, Dhiman (Research on Chemical Intermediates, 2018)
A series of 2-aryl-4-((4-aryl-1H-1,2,3-triazol-1-yl)methyl)thiazole derivatives (8a-p) have been synthesized. The structure of the newly synthesized compounds was determined by spectral analysis. The title compounds were screened for their preliminary antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB, ATCC 25177) and Mycobacterium bovis BCG (BCG, ATCC 35743). Further, the synthesized compounds were screened for antimicrobial activity against standard Gram-negative bacteria Escherichia coli (NCIM 2576) and Pseudomonas flurescence (NCIM 2059) and Gram-positive bacteria Staphylococcus aureus (NCIM 2602) and Bacillus subtilis (NCIM 2162). Among all the synthesized compounds, 8a-c, f-h, m exhibited good activity against dormant M. bovis BCG strain. Compounds 8h, j exhibited good activity against all tested bacterial strains. All active compounds were screened for cytotoxicity and found inactive. Their high potency and promising antimycobacterial activity suggest that these compounds could serve as good leads for further optimization and development.
Keywords: 1; 2; 3-Triazole; antibacterial activity; Antitubercular activity; Thiazole

Synthesis and biological evaluation of novel triazole-biscoumarin conjugates as potential antitubercular and anti-oxidant agents - Danne, Ashruba B. (Research on Chemical Intermediates, 2018)
The synthesis of a new series of triazole-biscoumarin conjugates by using a molecular hybridization approach is described. The newly synthesized compounds 6a–k were evaluated for their in vitro antitubercular activity against active and dormant Mtb H37Ra and anti-oxidant activity against DPPH radical scavenging. Molecular docking simulations for the antitubercular activity showed that the conjugates 6a–k bind in the pocket of the DprE1 enzyme. Most of the conjugates displayed good antitubercular activity against both the active and dormant Mtb H37Ra strain. The compound 6h displayed very good antitubercular activity against dormant Mtb H37Ra with an IC50 value of 1.44 μg/mL. Most of the synthesized conjugates exhibit excellent anti-oxidant activity with an IC50 of less than the standard BHT. Compound 6b is the most active among all the conjugates with an IC50 value of 08.17 ± 0.11 μg/mL. The molecular docking study shows good agreement between the observed antitubercular activity and the binding affinity.
Keywords: 1; 2; 3-triazoles; Anti-oxidant activity; Antitubercular activity; Biscoumarins; Molecular docking

Synthesis and biological evaluation of some bicyclic [2-(2,4-dimethylphenylthio)phenyl] aniline and its amide derivatives as potential antitubercular agents - Patil, Yogesh; Shingare, Ramesh (Journal of Chemical Sciences, 2018)
In the present investigation, a series of bicyclic [2-(2,4-dimethylphenylthio)phenyl] aniline analogues were synthesized and characterized by IR, NMR (1H and 13C) and mass spectra. All newly synthesized 15 compounds were inspected for their in vitro antitubercular activity against Mycobacterium tuberculosis (MTB) H37Ra in both active and dormant state using an established XTT Reduction Menadione assay (XRMA). The titled compounds exhibited minimum inhibitory concentration (MIC90) ranging from 0.05 to >30 (μg/mL). The potent four compounds were further evaluated in THP-1 infection model where they demonstrated significant antitubercular activity. All the ex vivo active were further evaluated for cytotoxic activity against THP-1, MCK7 and HeLa cell lines in order to check selectivity index. All compounds were further screened against four different bacteria to assess their selectivity towards MTB. These derivatives could be considered as a precursor structure for further design of antituberculosis agent.
Keywords: 4-dimethylphenylthio)phenyl] aniline; antituberculosis activity; Cytotoxicity; [2-(2

Synthesis and biological evaluation of some new tricyclic pyrrolo[3,2-e]tetrazolo[1,5-c]pyrimidine derivatives as potential antitubercular agents - Patil, Yogesh; Shingare, Ramesh; Choudhari, Amit; Borkute, Rachana; Sarkar, Dhiman; Madje, Balaji R. (Archiv Der Pharmazie, 2018)
A series of new tricyclic pyrrolo[3,2-e]tetrazolo[1,5-c]pyrimidines 8a-l were synthesized and characterized by IR, NMR (H-1 and C-13), and mass spectral analysis. The newly synthesized compounds 8a-l were inspected for their in vitro antitubercular activity against Mycobacterium tuberculosis (MTB) H37Ra using an established XTT reduction menadione assay (XRMA). The title compounds exhibited minimum inhibitory concentrations (MIC90) ranging from 0.09 to >30g/mL. Five compounds (8c, 8i-l) were further confirmed for their dose-dependent effect against MTB. These compounds were evaluated in the THP-1 infection model, where 8i (MIC90=0.35g/mL), 8j (MIC90=1.17g/mL), 8k (MIC90=2.38g/mL), and 8l (MIC90=1.17g/mL) demonstrated significant antitubercular activity. All the ex vivo active compounds showed insignificant cytotoxicity against the human cancer cell lines, HeLa, MCF-7, and THP-1. Inactivity of all these compounds against Gram positive and Gram negative bacteria indicates their specificity. Molecular docking studies in the active site of the sterol 14alpha-demethylase (CYP51) enzyme revealed a similar binding mode to the native ligand in the crystal structure, thereby helping to understand the ligand-protein interactions and to establish a structural basis for inhibition of MTB. The results suggest novel pharmacophores as selective and specific inhibitors against MTB that can be explored further to synthesize lead compounds against tuberculosis. In summary, the results clearly indicate the identification of some novel, selective, and specific inhibitors against MTB that can be explored further for potential antitubercular drugs.
Keywords: 2-e]tetrazolo[1; 5-c]pyrimidine; Antituberculosis; Cytotoxicity; Molecular docking; tricyclic pyrrolo[3

Synthesis, biological evaluation, and molecular docking study of pyridine clubbed 1,3,4-oxadiazoles as potential antituberculars - Desai, N. C. (Synthetic Communications, 2018)
A series of pyridine clubbed 1,3,4-oxadiazole derivatives were efficiently synthesized, characterized by standard spectral techniques and evaluated for their in vitro antitubercular activity against Mycobacterium tuberculosis (MTB) H37Ra and Mycobacterium bovis BCG in active and dormant state using an established methods. Compounds 5a, 5m, and 5t were identified as the most active compounds against MTB. Molecular docking was performed against MTB enoyl-ACP (CoA) reductase (FabI/ENR/InhA) enzyme to predict the binding modes and affinity. The theoretical predictions from molecular docking could establish a link between the observed biological activity and the binding affinity shedding light into specific bonded and non-bonded interactions influencing the activity. The active compounds were studied for cytotoxicity against three cell lines and were found to be non-cytotoxic. Specificity of these compounds was checked by screening them for their antibacterial activity against four bacterial strains.
Keywords: antibacterial activity; antituberculosis activity; cytotoxicity activity

Synthesis and antimycobacterial evaluation of new 5-(1-benzyl-1H-1,2,3-triazol-4-yl)-4-methyl-2-arylthiazole derivatives - Shinde, Vikas; Mahulikar, Pramod; Mhaske, Pravin C.; Chakraborty, Shakti; Choudhari, Amit; Phalle, Siddharth; Choudhari, Prafulla; Sarkar, Dhiman (Medicinal Chemistry Research, 2019)
A new series of 5-(1-benzyl-1H-1,2,3-triazol-4-yl)-4-methyl-2-arylthiazole derivatives, 6a-w have been synthesized by click reaction of substituted benzylazide, 5a-d with 5-ethynyl-4-methyl-2-substituted phenylthiazole, 4a-f. The starting compounds 4-ethynyl-2-substituted phenylthiazole (4a-f) were synthesized from the corresponding thiazole aldehyde by using the Ohira-Bestmann reagent. The structure of the synthesized compounds was determined by spectral analysis. All the synthesized compounds were screened for their preliminary antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB, ATCC 25177). Most of the synthesized compounds reported good activity against M. tuberculosis H37Ra strain with IC50 range of 0.58-8.23 mu g/mL. Compounds 6g and 6k reported good antitubercular activity with MIC90 values of 4.71 and 2.22 mu g/mL, respectively. Potential antimycobacterial activity suggested that these compounds could serve as good lead compounds for further optimization and development of a newer antitubercular candidate. [GRAPHICS] .
Keywords: 1; 2; 3-Triazole; Antitubercular activity; Molecular docking; Ohira-Bestmann reagent; Thiazole

Synthesis and biological evaluation of 2,4,5-trisubstituted thiazoles as antituberculosis agents effective against drug-resistant tuberculosis - Karale, Uttam B.; Krishna, Vagolu Siva; Krishna, E. Vamshi; Choudhari, Amit S.; Shukla, Manjulika; Gaikwad, Vikas R.; Mahizhaveni, B.; Chopra, Sidharth; Misra, Sunil; Sarkar, Dhiman; Sriram, Dharmarajan; Dusthackeer, V. N. Azger; et al. (European Journal of Medicinal Chemistry, 2019)
The dormant and resistant form of Mycobacterium tuberculosis presents a challenge in developing new anti-tubercular drugs. Herein, we report the synthesis and evaluation of trisubstituted thiazoles as antituberculosis agents. The SAR study has identified a requirement of hydrophobic substituent at C2, ester functionality at C4, and various groups with hydrogen bond acceptor character at C5 of thiazole scaffold. This has led to the identification of 13h and 13p as lead compounds. These compounds inhibited the dormant Mycobacterium tuberculosis H37Ra strain and M. tuberculosis H37Rv selectively. Importantly, 13h and 13p were non-toxic to CHO cells. The 13p showed activity against multidrug-resistant tuberculosis isolates. (C) 2019 Elsevier Masson SAS. All rights reserved.

Synthesis and biological evaluation of new 4-(4-(1-benzyl-1H-1,2,3-triazol-4-yl)phenyl)-2-phenylthiazole derivatives - Shinde, Vikas; Mhaske, Pravin C.; Singh, Aakriti; Sarkar, Dhiman; Mahulikar, Pramod (Journal of Heterocyclic Chemistry, 2019)
A novel series of 4-(4-(1-benzyl-1H-1,2,3-triazol-4-yl)phenyl)-2-substitutedthiazole derivatives (8a-l) have been synthesized by [3 + 2] cycloaddition reaction of 4-(4-ethynylphenyl)-2-substitutedthiazole with substituted benzyl azide in aqueous DMF. Starting compounds 4-(4-ethynylphenyl)-2-substitutedthiazole (6a-d) were synthesized by reaction of 4-(2-substitutedthiazol-4-yl)benzaldehyde with Ohira-Bestmann reagent in methanol. The structures of these novel triazole-thiazole clubbed derivatives were confirmed by the spectral analysis. The title compounds (8a-l) were tested for antimycobacterial activity against Mycobacterium tuberculosis H37Ra active and dormant (MTB, ATCC 25177) and antimicrobial activity against standard Gram-positive bacteria, Staphylococcus aureus (NCIM 2602) and Bacillus subtilis (NCIM 2162), and Gram-negative bacteria, Escherichia coli (NCIM 2576) and Pseudomonas flurescence (NCIM 2059). Compounds 8a, 8b, 8c, and 8h reported good activity against B subtilis, compounds 8a, 8b, and 8c showed good activity against S aureus, and compound 8b showed good activity against dormant M tuberculosis H37Rv strain. Compounds 8b and 8c found more potent against Gram positive and dormant M tuberculosis H37Rv strains. These novel triazole-thiazole clubbed analogues found to be a capable leads for further optimization and development.

Synthesis of new 1,3,4-oxadiazole and benzothiazolylthioether derivatives of 4-arylmethylidene-3-substituted-isoxazol-5(4H)-one as potential antimycobacterial agents - Chavan, Abhijit P.; Deshpande, Rujuta R.; Borade, Nandkumar A.; Shinde, Abhijit; Mhaske, Pravin C.; Sarkar, Dhiman; Bobade, Vivek D. (Medicinal Chemistry Research, 2019)
A new series of 4-[(substituted benzylidene)-3-[(5-(pyridine-4-yl)-1,3,4-oxadiazole-2-ylthio)-methyl]i soxazol-5(4H)-one (6a-g) and 4-(substituted benzylidene)-3-((benzo[d]thiazol-2-ylthio)methyl)isoxazol-5(4H)-one (8a-g) was synthesized. All the synthesized compounds were screened for antitubercular activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743) and antibacterial activity against Escherichia coli (NCIM 2576), Pseudomonas flurescence (NCIM 2059), Staphylococcus aureus (NCIM 2602), Bacillus subtilis (NCIM 2162). Amongst the synthesized 1,3,4-oxadiazole and benzothiazoyl thioether derivatives, compounds 6b and 8b showed excellent antimycobacterial activity and compounds 6b, 8a, 8b, and 8d showed excellent antibacterial activity against all tested antibacterial strains. The synthesized compounds were further evaluated for their cytotoxic activity against the HCT 116 and HeLa cancer cell lines. The 1,3,4-oxadiazole and benzothiazoyl thioether derivatives 6a-g and 8a-g did not show cytotoxicity.
Keywords: 1; 3; 4-Oxadiazole; antibacterial activity; Antitubercular activity; Benzothiazol; Isoxazol-5(4H)-one; Thioeteher

Synthesis and antimycobacterial screening of new 4-(4-(1-benzyl-1H-1,2,3-triazol-4-yl)-1-phenyl-1H-pyrazol-3-yl)quinoline derivatives - Thakare, Prashant P.; Walunj, Yogesh; Chavan, Abhijit; Bobade, Vivek D.; Sarkar, Dhiman; Mhaske, Pravin C. (Journal of Heterocyclic Chemistry, 2020)
A new series of 4-(4-(1-benzyl-1H-1,2,3-triazol-4-yl)-1-phenyl-1H-pyrazol-3-yl)quinoline (6a-t) have been synthesized by a click reaction of 4-(4-ethynyl-1-phenyl-1H-pyrazol-3-yl)quinoline (4a-d) with a substituted benzyl azide (5a-e). The starting alkyne derivatives4a-dare obtained from Bestmann-Ohira reaction of 1-phenyl-3-(quinolin-4-yl)-1H-pyrazole-4-carbaldehyde and dimethyl(1-diazo-2-oxopropyl)phosphonate. The newly synthesized compounds are screened againstM. tuberculosisH37Ra dormant and active,Escherichia coli,Pseudomonas fluorescence,Staphylococcus aureusandBacillus subtilisstrains at 30 mu g/mL concentration. Most of the screened compounds showed good to moderate antibacterial activity againstS. aureus,B. subtilis, andMycobacterium tuberculosisH37Ra strains. The synthesized derivatives of quinolinyl-pyrazole-4-carbaldehyde and quinolinyl-pyrazole-4-ethyne reportd good to moderate activity against both strains ofM. tuberculosisH37Ra. Ten derivatives of quinolinyl-pyrazole presented good activity againstB. subtilis. These results suggested that further optimization and development of quinolinyl-pyrazolyl-1,2,3-triazole moeity could serve as lead compounds for antimycobacterial activity.

Synthesis and cell imaging applications of fluorescent mono/di/tri-heterocyclyl-2,6-dicyanoanilines (vol 27, pg 979, 2017) - Pisal, Mahesh M.; Annadate, Ritesh A.; Athalye, Meghana C.; Kumar, Deepak; Chavan, Subhash P.; Sarkar, Dhiman; Borate, Hanumant B. (Bioorganic & Medicinal Chemistry Letters, 2021)

Synthesis of new 2-(thiazol-4-yl)thiazolidin-4-one derivatives as potential anti-mycobacterial agents - Abhale, Yogita K.; Shinde, Abhijit; Shelke, Monika; Nawale, Laxman; Sarkar, Dhiman; Mhaske, Pravin C. (Bioorganic Chemistry, 2021)
To search for potent antimycobacterial lead compounds, a new series of 3-substituted phenyl-2-(2-(substituted phenyl)thiazol-4-yl) thiazolidin-4-one (5a-t) derivatives have been synthesized by the condensation of 2 substituted phenyl thiazole-4-carbaldehyde with aromatic amine followed by cyclocondensation with thioglycolic acid. The structure of the newly synthesized 2-(thiazol-4-yl)thiazolidin-4-one derivatives were characterized by the spectroscopic analysis. The synthesized compounds were screened for antimycobacterial activity against Mycobacterium tuberculosis H37Ra (MTB) (ATCC 25177) and Mycobacterium bovis BCG (BCG, ATCC 35743). Most of the 2-(thiazol-4-yl)thiazolidin-4-one derivatives showed good to excellent antimycobacterial activity against both the Mtb strains. Nine derivatives 5c, 5g, 5j, 5m, 5n, 5o, 5p, 5s, and 5t showed excellent activity against M. bovis BCG with MIC 4.43 to 24.04 mu M were further evaluated for the cytotoxicity activity against HeLa A549, and HCT-116 cell lines and showed no significant cytotoxic activity at the maximum concentration evaluated. The potential antimycobacterial activities enforced that the thiazolyl-thiazolidin-4-one derivatives could lead to compounds that could treat tuberculosis.
Keywords: Cytotoxicity; Mycobacterium tuberculosis; Thiazole; Thiazolidin-4-one

Synthesis and antimycobacterial screening of a novel series of alpha-amino acids containing thiazole linker - Nalawade, Jitendra L.; Mhaske, Pravin C.; Shinde, Abhijit D.; Chavan, Abhijit P.; Abhale, Yogita K.; Sarkar, Dhiman; Bobade, Vivek D. (ARKIVOC, 2022)
A small focused library of uncommon (S)-2-amino-3-(4-(((4-methyl-2-arylthiazol-5-yl)methyl)amino)phenyl) propanoic acid (5a-e) and (S)-2-amino-3-(4-(((2-arylthiazol-4-yl)methyl)amino)phenyl)propanoic acid (9a-d) derivatives have been efficiently synthesized by employing molecular simplification. The title compounds were screened for inhibitory activity against Mycobacterium tuberculosis H37Ra (MTB) and Mycobacterium bovis (BCG) strains. The cytotoxicity study was conducted against primary Human Umbilical Vein Endothelial Cells (HUVECs), on two different human tumor cells HeLa, and HCT 116 and was observed non-toxic to host cells.
Keywords: Amino acid; antibacterial activity; Cytotoxicity; Mycobacterium tuberculosis; synthesis; Thiazole

Synthesis of new thiazole and pyrazole clubbed 1,2,3-triazol derivatives as potential antimycobacterial and antibacterial agents - Jagadale, Shivaji M.; Abhale, Yogita K.; Pawar, Hari R.; Shinde, Abhijit; Bobade, Vivek D.; Chavan, Abhijit P.; Sarkar, Dhiman; Mhaske, Pravin C. (Polycyclic Aromatic Compounds, 2022)
New series of 4-methyl-2-(4-substituted phenyl)-5-(4-((4-(4-substituted phenyl)-1H-1,2,3-triazol-1-yl)methyl)-1-phenyl-1H-pyrazol-3-yl)thiazole, 6a-t and 4-(1,3-diphenyl-1H-pyrazol-4-yl)-1-((1,3-diphenyl-1H-pyrazol-4-yl)methyl )-1H-1,2,3-triazole, 11a-o derivatives have been synthesized by applying copper-catalyzed [3 + 2] cycloaddition reaction. The newly synthesized 1,3-thiazolyl-pyrazolyl-1,2,3-triazole (6a-t) and bis-pyrazolyl-1,2,3-triazole (11a-o) derivatives were screened for in vitro antimycobacterial activity against M. Tuberculosis H37Ra dormant and active and antibacterial activity against four pathogenic bacteria, E. coli (NCIM 2576), P. flurescence (NCIM 2059), S. aureus (NCIM 2602) and B. subtilis (NCIM 2162). Compounds 6a, 6f, 6j, 11e and 11m showed good activity against M tuberculosis H37Ra Active strain, also compounds 6g, 6h, 11f, 11n and 11o showed good activity against M tuberculosis H37Ra Dormant strain. Compounds 6b, 6i, 6l, 6o, 6r, 11k, 11l and 11m showed good activity against B. subtilis with IC50 1.99-2.96 mu g/mL. The antibacterial activity of thiazolyl-pyrazolyl-1,2,3-triazole and bis-pyrazolyl-1,2,3-triazole derivatives suggested that, these derivatives could lead to new compounds for treatment against bacterial infection.
Keywords: 123-Triazole; antibacterial activity; antimycobacterial activity; Pyrazole; Thiazole

Synthesis and antimicrobial evaluation of novel 2'-aryl-4-aryl-2,4'-Bisthiazole and 2'-aryl-4-Pyridyl-2,4'-bisthiazole derivatives as potential antibacterial agents - Nalawade, Jitendra; Shinde, Abhijit; Abhale, Yogita K.; Nandurkar, Yogesh; Bobade, Vivek D.; Sarkar, Dhiman; Mhaske, Pravin C. (Polycyclic Aromatic Compound, 2024)
In continuation of our research work to explore bisthiazole derivatives as potential antimicrobial agents, herein we reported the synthesis of a series of novel 2'-aryl-4-aryl-2,4'-bisthiazole (7a-t) and 2'-aryl-4-pyridyl-2,4'-bisthiazole (9a-l) by cyclocondensation of 2-aryl thiazole-4-carbothioamide 5a-d with 2-bromo-1-arylethanone (6a-e) and bromo-1-(pyridin-2/3/4-yl)ethanone (8a-c), respectively. These novel candidates were evaluated in vitro for their antibacterial potential against four pathogenic bacteria, Escherichia coli (NCIM 2576), Pseudomonas flurescence (NCIM 2059), Staphylococcus aureus (NCIM 2602), and Bacillus subtilis (NCIM 2162). The synthesized compounds were also screened for their in vitro antifungal activity against Candida albicans (NCIM 3100). Among them, compounds 7b, 9d, 9 g, 9i, and 9 l exhibited excellent antibacterial activity with MIC 2.1 to 12.3 mu g/mL against all tested strains. Most of the compounds reported moderate antifungal activity. The pyridine ring-substituted bisthiazole reported good to excellent antibacterial activity as compared to phenyl ring-substituted bisthiazole. The potential antibacterial activity suggested that bisthiazole derivatives could assist in the development of lead compounds to treat microbial infections.
Keywords: 24'-bisthiazole; antibacterial activity; Antifungal activity; cyclocondensation

Synthesis, biological screening, and molecular docking of hybrid pyrazole scaffolds for antitubercular and antimicrobial activity - Bavishi, Abhay; Vala, Hardev; Radadiya, Ashish; Swami, Sagar; Thakrar, Shailesh; Sarkar, Dhiman; Shah, Anamik (ChemistrySelect, 2025)
This study reports the synthesis, characterization, and docking analysis of 21 novel compounds, including asymmetric dihydropyridines (4a-4o) and chalcones (6a-6f), derived from coupling 1,3-(substituted)-diphenyl-1H-pyrazole-4-carbaldehyde with active methylene compounds and 3-acetyl-4-hydroxycoumarin, respectively. Structural confirmation was achieved through 1H and 13C NMR, IR, and mass spectrometry. Biological screening against mycobacterium tuberculosis H37Ra identified compounds 4b, 4d, 4f, 4g , 4i, 4k, 6e, and 6f as significant antitubercular agents. Antibacterial evaluation at 30 mu g/mL showed selective inhibition of gram-positive bacteria, with compound 6e active against Staphylococcus aureus and Bacillus subtilis, and 6f showing activity specifically against S. aureus. Docking studies indicated effective InhA binding (Delta G = -3.52 to -7.27 kcal/mol) and inhibition constants ranging from 2640 to 4.71 mu M. Key binding interactions with residues TYR156 and ILE192 were observed, enhancing affinity, particularly for compound 6e. The SAR analysis emphasized the enhanced antitubercular potency of 2-chloroacetyl and 2,4-dichlorobenzoyl substitutions in the dihydropyridine series, while in the chalcone series, specific substitutions, such as the 3-nitro substitution in 6e, enhance antitubercular and antimicrobial potency due to stronger hydrogen bonding and increased polar surface area, while the 4-fluoro substitution in 6f confers selective activity against S. aureus.
Keywords: 1; 4-dihydropyridine; 4-hydroxy coumarin; Biological activity; In silco studies; Pyrazole